How still is still? Exploring human standstill for artistic applications. (1st January 2014) - Jensenius, Alexander Refsum; Bjerkestrand, Kari Anne Vadstensvik; Johnson, Victoria
In this paper, we present the results of a series of observation studies of the three team members standing still for ten minutes at a time. The aim has been to understand more about people's ability to stand still, and to develop a heightened sensitivity for micromovements and how they might be used in music and dance performances. The quantity of motion, calculated from motion capture data using a head marker, was remarkably similar for each person who stood still. The 'best' results – that is, the least movement – were obtained when the subject set his/her feet at the width of the shoulders, locked the knees, and kept the eyes open. No correlation was found between quantity of motion and type of mental coping strategy, though we remain convinced that mental strategies influence the experience of standing still. These findings will be used to inform the development of a stage performance focused on micromovements.